Stress hyperglycemia is associated with poor prognosis in critically ill patients with cardiogenic shock - Tian, Jing; Zhou, Tao; Liu, Zijuan; Dong, Yan; Xu, Hongyang (Frontiers in Endocrinology, 2024)
Background Stress hyperglycemia is now more common in intensive care unit (ICU) patients and is strongly associated with poor prognosis. Whether this association exists in critically ill patients with cardiogenic shock (CS) is unknown. This study investigated the prognostic relationship of stress hyperglycemia on critically ill patients with CS.We included 393 critically ill patients with CS from the MIMIC IV database in this study and categorized the patients into four groups based on quartiles of Stress hyperglycemia ratio (SHR).We assessed the correlation between SHR and mortality using restricted cubic spline analysis and Cox proportional hazards models. The primary outcomes observed were ICU mortality and hospitalization mortality.The mean age of the entire study population was 68 years, of which 30% were male (118 cases). There was no significant difference between the four groups in terms of age, gender, BMI, and vital signs (P＞0.05). There was an increasing trend in the levels of lactate (lac), white blood cell count (WBC), glutamic oxaloacetic transaminase (AST), glucose and Hemoglobin A1C (HbA1c) from group Q1 to group Q2, with the greatest change in patients in group Q4 (P<0.05) and the patients in group Q4 had the highest use of mechanical ventilation, the longest duration of mechanical ventilation, ICU stay and hospital stay. After adjusting for confounders, SHR was found to be strongly associated with patient ICU mortality, showing a U-shaped relationship.In critically ill patients with CS, stress hyperglycemia assessed by SHR was significantly associated with patient ICU mortality.